The feeling of familiarity for music in patients with a unilateral temporal lobe lesion: A gating study. (October 2015) - Huijgen, Josefien; Dellacherie, Delphine; Tillmann, Barbara; Clément, Sylvain; Bigand, Emmanuel; Dupont, Sophie; Samson, Séverine
Abstract: Previous research has indicated that the medial temporal lobe (MTL), and more specifically the perirhinal cortex, plays a role in the feeling of familiarity for non-musical stimuli. Here, we examined contribution of the MTL to the feeling of familiarity for music by testing patients with unilateral MTL lesions. We used a gating paradigm: segments of familiar and unfamiliar musical excerpts were played with increasing durations (250, 500, 1000, 2000, 4000 ms and complete excerpts), and participants provided familiarity judgments for each segment. Based on the hypothesis that patients might need longer segments than healthy controls (HC) to identify excerpts as familiar, we examined the onset of the emergence of familiarity in HC, patients with a right MTL resection (RTR), and patients with a left MTL resection (LTR). In contrast to our hypothesis, we found that the feeling of familiarity was relatively spared in patients with a right or left MTL lesion, even for short excerpts. All participants were able to differentiate familiar from unfamiliar excerpts as early as 500 ms, although the difference between familiar and unfamiliar judgements was greater in HC than in patients. These findings suggest that a unilateral MTL lesion does not impair the emergence of the feeling of familiarity. We also assessed whether the dynamics of the musical excerpt (linked to the type and amount of information contained in the excerpts) modulated the onset of the feeling of familiarity in the three groups. The difference between familiar and unfamiliar judgements was greater for high than for low-dynamic excerpts for HC and RTR patients, but not for LTR patients. This indicates that the LTR group did not benefit in the same way from dynamics. Overall, our results imply that the recognition of previously well-learned musical excerpts does not depend on the integrity of either right or the left MTL structures. Patients with a unilateral MTL resection may compensate for the effects of unilateral damage by using the intact contralateral temporal lobe. Moreover, we suggest that remote semantic memory for music might depend more strongly on neocortical structures rather than the MTL. Highlights: Unilateral MTL lesion does not impair musical familiarity processing. The emergence of the feeling of familiarity is triggered as early as 500 ms. Musical dynamics modulate familiarity judgments in RTR patients and HC.